Factors Related To Anemia Among Female Students City - Lukito, Nurul Uzlifatil Jannah; Maryani, Deni; Purnama, Yetti; Himalaya, Dara (JURNAL KEBIDANAN, 2025)
Adolescent girls have a higher risk of developing anemia than adolescent boys, Based on the 2018 National Basic Health Research, 48.9% of adolescent girls in Indonesia are anemic. Adolescents who suffer from anemia when they become pregnant are at risk of giving birth to low birth weight (LBW) and stunting. Iron nutritional anemia is one of the main causes of anemia, including due to insufficient intake of iron-source foods. namely BMI, Mid Upper Arm Circumference (MUAC),  and tea and coffee consumption. This research aims to determine the factors associated with hemoglobin levels in adolescent girls at SMK 3 Bengkulu City. Data analysis used regression testing. The sample for this research was 73 respondents who were selected used the purposive sampling technique. sampling is carried out in accordance with the inclusion criteria. validity and reliability tests of questionnaires are taken from the results of previous studies. Data analysis used the Pearson product moment correlation test. The results of the research, namely the relationship between BMI and hemoglobin levels, obtained univariate results hemoglobin in the interval 8.0-11.9 gr/dl was (35.61%) low hemoglobin and the interval 12 gr/dl was (64.38%) normal hemoglobin category, BMI (4.10%) underweight, (17.80%) underweight, (69.86%) normal, and (8.21%) overweight.   MUAC: (43,83%) Calorie energy deficiency, (56,16%) non Calorie energy deficiency, Tea/Coffee Consumption (58,90%) lower, (41,10%) currently, and bivariate result (p = 0.001–0.05), so there was an influence on BMI and hemoglobin levels. The results of the analysis regarding the relationship between MUAC and hemoglobin levels obtained results (p = 0.001– 0.05), so there was an influence on MUAC and hemoglobin levels. The results of the analysis regarding the relationship between tea/coffee consumption and hemoglobin levels obtained results (p = 0.011 0.05), so there was an influence on tea/coffee consumption and hemoglobin levels in young women at SMK 3 Bengkulu City. The conclusion of this research is that there is an influence on BMI, MUAC, and tea/coffee consumption on hemoglobin levels.